Sovereignty under trial: crisis in Augustine of Hippo’s political theology, between Carl Schmitt and Erik Peterson - Grassi, Martin (Argumentos - Revista de Filosofia, 2023)
In this paper I will argue that the concept of crisis is at the heart of Political Theology by focusing on the major work of Augustine of Hippo, The City of God. Augustine’s strategy is to gather both medical and theological meanings of crisis to argue for the unique sovereignty of the One God, the only one that decides and judges over the critical course of history and the One that will bring everything to an end by His Final Judgement. The focus on Augustine’s treatise will also show how the Political Theology quarrel between Carl Schmitt and Erik Peterson should be examined once again, mainly to redefine the concept of sovereignty by the concept of crisis, for to be considered a sovereign is in itself something to be decided on.